تقويم تبني المنظمات السورية للتسويق الإلكتروني "دراسة حالة شركة جود التجارية" (Latakia University Journal - Economic and Legal Sciences Series, 2018)
نتيجة التطور التكنولوجي الكبير في عالم اليوم وانتشار تقنيات الأعمال الإلكترونية والعمل فيها بشكل واسع في مختلف أنحاء العالم كان لابد لمنظمات الأعمال من مواكبة هذا التطور الكبير في سبيلالبقاء في الأسواق واستمراريتها. حيث يعد انتشار البيئة الإلكترونية والعمل فيها جزء من حياة الأفراد. وقد انتشر مفهوم التسويق الإلكتروني كجزء هام من العمل في هذه البيئة. ولأن هذا المفهوم يعد العمل فيه حديث نسبياً في البيئة السورية كان هناك العديد من العوامل التي تحد من انتشار استخدامه واستثماره بشكل يساعد المنظمات في سورية على التقدم والعمل فيه. لهذا جاء هذا البحث لدراسة العوامل التي تؤثر على تبني المنظمات السورية للتسويق الإلكتروني.ومن بين العوامل التي تمت دراستها في هذا البحث مدى توفر بنية تحتية مناسبة لاستخدام التسويق الإلكتروني وتبنيه من قبل المنظمات السورية، وتوافر كفاءات بشرية قادرة على العمل في التسويق الإلكتروني ونجاحه من قبل المنظمات السورية، بالإضافة إلى الثقافة التنظيمية التي تتبعها المنظمات السورية، وقد تمت دراسة هذا البحث من خلال دراسة حالة تم فيها توزيع (110) استبانة على الموظفين في شركة جود التجارية. As a result of huge technological development now a days and spreading techniques of electronical jobs and using them widely all over the world, it was necessary for organizations of jobs to keep up with this great development in order to stay in markets and be continuous. Spreading the electronic environment and working with it is considered part of individuals’ life. The principle of electronic marketing has spread as an important part for working in this environment. And because the working with this principle is considered modern relatively in the Syrian environment there were many factors that reduce of spreading its use and making use of in a way to help organizations in Syria to progress and work with it. So this research has been for studying factors which affect adopting of Syrian organizations the electronic marketing. and the factors which had been studied in this research is how available is the suitable infrastructure for using the electronic marketing and adopting it by the organizations and existence of human qualifications who are able for working in the electronic marketing and the success by the organizations in addition to the ordering education which are followed by the organizations and this research had been studied through the case study which distributed (110) questioner about the commercial company of Joud.